Academic freedom or socialism of state. The dilemma of the students of the Guadalajara University in 1933-1937 - Martínez Moya, Armando (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
The University of Guadalajara was a sand of an antagonistic conflict staged by two political - ideological tendencies that they thought about how to influence in the guidelines of the institution and finally in its control: the autonomic area, defending university autonomy and the academic freedom, and the socialistic tendency, defending the reform of this sign promulgated by the diet of the Mexican Revolution. This situation emerged in a movement that in an intermittent way populated the university between 1933-1937. In this work, there are tackled some aspects of the episode and its definitive ending. This subjectmatter has been as a rule an apologetic topic for the official history of the University, since the student movement appears as one anniversary of its foundation. In this text it is a question of demonstrating, through histories that some protagonists wrote, that the history shows other explanations.